2021
DOI: 10.3390/en14102819
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analytical Modeling for Optimal, On-Design Performance of Ejector for Simulating Heat-Driven Systems

Abstract: This paper describes an ejector model for the prediction of on-design performance under available conditions. This is a direct method of calculating the optimal ejector performance (entrainment ratio or ER) without the need for iterative methods, which have been conventionally used. The values of three ejector efficiencies used to account for losses in the ejector are calculated by using a systematic approach (by employing CFD analysis) rather than the hit and trial method. Both experimental and analytical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…The efficiency defects of the compressor, condenser, expansion valve, and evaporator are depicted by Equations ( 17)- (20), respectively:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The efficiency defects of the compressor, condenser, expansion valve, and evaporator are depicted by Equations ( 17)- (20), respectively:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The idea of energy efficiency is reinforced by a similar case study from Italy, where an office building cut short its energy usage and emission to an extent of about 40% solely by retrofitting [15,16]. Another Canadian study came up with the conclusion that energy consumption can be reduced by 45%, only by insulating the roof and walls and replacing the windows of an office building in Vancouver city.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that decreasing the wetness of the secondary inlet flow could potentially optimize system performance, signified by a substantial increase in the entrainment ratio. Riaz et al [10] similarly conducted direct analytical modeling for optimal, on-design performance of an ejector for simulating heat-driven systems. Li et al [11] examined the effect of different pressure conditions on shock waves in a supersonic steam ejector, demonstrating that the intensity and number of oblique shock waves in the diffuser increase with an elevation in motive pressure and suction pressure, or a reduction in discharge pressure.…”
Section: Introductionmentioning
confidence: 99%